2022
DOI: 10.3390/ijms231911955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL10 and TGFB1 Promoter Polymorphisms on Serum Cytokine Levels in Development and Severity of RA

Abstract: In our study, we focused on the role of the immunosuppressive cytokines TGF-β1 and IL-10 in RA and, in particular, the influence of the IL10-1082 A/G (rs1800896) and TGFB1-509C/T (rs1800469) promoter polymorphisms on their levels as a prerequisite for RA and disease activity clinical features. We found significantly higher IL-10 and lower TGF-β1 serum levels in women with RA than in controls. Patients who carried the -1082AA and AG genotypes had significantly higher levels of lnIL-10 compared to GG in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…However, Min-yu-tu et al showed that the CC-genotype of TGF-β could be protective in the progression of osteoporosis [ 48 ]. Liu C et al showed different findings from ours, where they found TT genotype and T-allele to be significantly associated with the susceptibility to OA, as other studies reported previously [ 30 , 49 , 50 , 51 ], although some studies did not find any association [ 52 ]. The position of TGF-β (-509C/T) is in the negative regulatory region of the TGF-β1 promotor.…”
Section: Discussioncontrasting
confidence: 83%
“…However, Min-yu-tu et al showed that the CC-genotype of TGF-β could be protective in the progression of osteoporosis [ 48 ]. Liu C et al showed different findings from ours, where they found TT genotype and T-allele to be significantly associated with the susceptibility to OA, as other studies reported previously [ 30 , 49 , 50 , 51 ], although some studies did not find any association [ 52 ]. The position of TGF-β (-509C/T) is in the negative regulatory region of the TGF-β1 promotor.…”
Section: Discussioncontrasting
confidence: 83%
“…Under the GCAS-approach, we found that the presence of FEIs on study entry ( ) versus their absence ( ) was strongly associated with four CTLA4 -assigned SNPs ( Figure 2 ), with rs231780 yielding the strongest signal ( p =2.3E-5) (Table 2), and suggestively associated with rs7528265, a SNP assigned to the interleukin (IL)-10 gene ( IL10 ) ( p =3.7E-3), which is closely linked to the three other Chr1 genes of the IL10 -superfamily, i.e., IL19 , IL20 , and IL24 encoding IL-19, IL-20, and IL-24 (Table 2). Like NOS2A and B3GNT2 , both CTLA4 and IL10 had previously been implicated in multiple AADs—including, e.g., RA, IDDM, and SLE 58 , 59 , 60 , 61 , 62 , 63 —but both had also been confirmed genetically to play a role in the development of FEIs. 20 , 22 , 23 Located on the long-arm of Chr2, CTLA4 comprises a telomerically-oriented, four-exon-containing transcription unit which spans sense-strand nucleotides 203,867,771–203,873,965 (GRCh38/hg38) ( Figure 3C ) and encodes the T-cell receptor—cytotoxic T-lymphocyte-associated-protein-4 (CTLA4)—that transduces inhibitory signals to down-regulate immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies demonstrated elevated serum inflammatory cytokines in women with RA with altered cytokine production depending on different treatment regimens [ 13 ]. However, investigation of immunoregulatory IL-10 and TGF-β1 in the same cohort revealed down-regulated systemic TGF-β1 but elevated IL-10 [ 8 ]. Also, we found that some single-nucleotide polymorphisms on promoter regions on IL10 and IL12B genes regulate serum cytokine expression and influence disease occurrence [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, investigation of immunoregulatory IL-10 and TGF-β1 in the same cohort revealed down-regulated systemic TGF-β1 but elevated IL-10 [ 8 ]. Also, we found that some single-nucleotide polymorphisms on promoter regions on IL10 and IL12B genes regulate serum cytokine expression and influence disease occurrence [ 8 , 9 ]. In this regard, the present study exploring the cytokine mRNA expression in the group of RA patients is a continuation of our previous investigations to understand better the involvement of inflammatory and regulatory cytokines in disease development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation